Using System Dynamics in Macroeconomics - K. Lawler; T. Vlasova; A. Moscardini (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2019)
In our previous studies, the authors argued that Economic Science in particular thesub –field of macroeconomics needed a profound reset and upgrade. It must use the systemic and cybernetic tools that are now available. This paper promotes a new paradigm and presents three examples that illustrate how a judicious application of systems theory can help to better understand the problem and offers a tool (System Dynamics) as a means of obtaining meaningful solutions.